Analiz soderzhaniya produktov lipoperoksidatsii v krovi lyzhnikov-gonshchikov razlichnoi sportivnoi kvalifikatsii - Dyatlov, D. A.; Volchegorsky, I. A.; Lvovskaya, E. I.; Sashenkov, T. I. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of the study was to analyse the distinctions in the content of the blood lipoperoxides in cross-country skiers of various qualification. 40 athletes of various qualification from the international sports masters to the first grade skiers aged from 16 to 25 years acted as subjects. Biochemical inspections had been performed after 2-3 days of the active rest. The obtained data alows to consider the indices of the lipoperoxidation in blood's plasma as one of the criteria for the objective evaluation of the athlete's special preparadeness level and his aerobiccapacities. Perhaps, the specific of training and competitional processes in skiing sport leads to the optimal intensification of the lipoperoxidation, when the content of lipoperoxides increases up to the meanings, optimizing the aerobic metabolism.